OPTIMIZATION OF LATHE BED TO REDUCE VIBRATION - PATEL, JIGNESH D; BHATT, Mr. ANTRIKSH (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
In this competitive market it has to be maximized the production with the help of machine tools. for increasing the production of machine tools by increasing spindle speeds have caused vibration in machine tools. The two main functional requirements of machine tool bed for machine tools to run at high speed are high structural stiffness and high damping, which cannot be satisfied simultaneously if conventional metallic materials such as cast iron are employed. Hence there is a need to replace cast iron with alternate materials to reduce the vibration of bed. The objective of this study is to improve the natural frequency and damping capability of machine tool bed using a material Epoxy-Glass. So in this study, a machine tool bed made of Epoxy-Glass is designed. Modal analyses were conducted numerically and experimentally to determine the modal frequencies, damping ratio.